The crystal structure of (E)-3-chloro-2-(2-(2-fluorobenzylidene)hydrazinyl)pyridine, C12H9ClFN3 - Wu Hui-Zhen; Min Li-Jing; Han Liang; Liu Xing-Hai; Sun Na-Bo (Zeitschrift für Kristallographie - New Crystal Structures)
C12H9ClFN3, monoclinic, C2/c (no. 15), a = 24.713(13) Å, b = 15.459(13) Å, c = 17.507(12) Å, β = 17.515(11)°, V = 4742(6) Å3, Z = 16, Rgt(F) = 0.0530, wRref(F2) = 0.1161, T = 113(2) K.